2010
DOI: 10.1017/s1751731110000170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricted feeding of prepubertal ewe lambs on growth performance and mammary gland development

Abstract: The aim of this study was to determine the effects of restricted feeding before puberty on growth performance and mammary gland development in replacement ewe lambs. At weaning, 72 Dorset ewe lambs were assigned to one of the three diets: an ad libitum control diet with medium-quality forage (MQF; diet A-MQF); a restricted diet with the same forage as A, but less feed concentrate (diet R-MQF); or a high-quality forage (HQF) diet (diet F-HQF). The quantity of concentrate offered to the group R-MQF and F-HQF ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Accordingly, plane of nutrition during gestation did not affect subsequent milk production in lambs (Umberger et al, 1985) and heifers (Lacasse et al, 1993). In a companion paper (Villeneuve et al, 2010), we reported that the mammary gland of restricted ewe lambs, groups R-MQF and F-HQF, was more developed than that of group A-MQF ewe lambs. Thus, the lower milk yield reported in this study supports the hypothesis of reduced mammary gland development.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Accordingly, plane of nutrition during gestation did not affect subsequent milk production in lambs (Umberger et al, 1985) and heifers (Lacasse et al, 1993). In a companion paper (Villeneuve et al, 2010), we reported that the mammary gland of restricted ewe lambs, groups R-MQF and F-HQF, was more developed than that of group A-MQF ewe lambs. Thus, the lower milk yield reported in this study supports the hypothesis of reduced mammary gland development.…”
Section: Discussionmentioning
confidence: 72%
“…The diets were offered for 75 days after weaning to cover the allometric phase of mammary gland development that occurred between 2 and 5.5 months of age according to Anderson (1975) and Johnsson and Hart (1985). After the restricted period, the animals had enough time to make a compensatory growth and reached ideal weight for breeding at 8 months of age (Villeneuve et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations